FOXP1-related intellectual disability syndrome: a recognisable entity. Issue 9 (22nd July 2017) - Meerschaut, Ilse; Rochefort, Daniel; Revençu, Nicole; Pètre, Justine; Corsello, Christina; Rouleau, Guy A; Hamdan, Fadi F; Michaud, Jacques L; Morton, Jenny; Radley, Jessica; Ragge, Nicola; García-Miñaúr, Sixto; et al.
Abstract : Background: Mutations in forkhead box protein P1 ( FOXP1 ) cause intellectual disability (ID) and specific language impairment (SLI), with or without autistic features (MIM: 613670). Despite multiple case reports no specific phenotype emerged so far. Methods: We correlate clinical and molecular data of 25 novel and 23 previously reported patients with FOXP1 defects. We evaluated FOXP1 activity by an in vitro luciferase model and assessed protein stability in vitro by western blotting. Results: Patients show ID, SLI, neuromotor delay (NMD) and recurrent facial features including a high broad forehead, bent downslanting palpebral fissures, ptosis and/or blepharophimosis and a bulbous nasal tip. Behavioural problems and autistic features are common. Brain, cardiac and urogenital malformations can be associated. More severe ID and NMD, sensorineural hearing loss and feeding difficulties are more common in patients with interstitial 3p deletions (14 patients) versus patients with monogenic FOXP1 defects (34 patients). Mutations result in impaired transcriptional repression and/or reduced protein stability. Conclusions: FOXP1 -related ID syndrome is a recognisable entity with a wide clinical spectrum and frequent systemic involvement. Our data will be helpful to evaluate genotype–phenotype correlations when interpreting next-generation sequencing data obtained in patients with ID and/or SLI and will guide clinical management.